Risk Factor Malariae in Indonesia (Faktor RisikoTerjadinya Malaria di Indonesia) - Pratoyo, Agung (Tadulako University, 2025)
The tropical disease malaria is still a special concern in the world and Indonesia. This evidence is contained in point 3.3. SDGs (Sustainable Development Goals) and the strategic plans of the Ministry of Health of the Republic of Indonesia are targeted 2030 the country will fulfill the elimination of this tropical disease (RI Ministry of Health, 2019). The design model used is a narrative review. The articles referred to are national and international journals related to risk factors for malaria. The inclusion criteria in this search are articles from Google Scholar and PubMed. Using search keywords, “risk factor”, “malaria”, and “Indonesia”. Based on the results of previous studies, it was found that several risk factors were most often encountered, namely the influence of the presence of livestock on the transmission of malaria, and the use of mosquito nets. After knowing the risk factors for malaria that occur in Indonesia, it can be used as a reference to improve the quality of the environment and livestock, and the government's program of distributing bed nets continues. After knowing the risk factors for malaria that occur in Indonesia, it can be used as a reference to improve the quality of the environment and livestock, and the government's program of distributing bed nets continues. Keywords : Risk factor; malariae; Indonesia.